Paraneoplastic Progressive Downbeat Nystagmus, Ataxia and Sensorineural Hearing Loss due to the ANTI-Kelch-11 Protein Antibody. Issue 2 (June 2021) - Kattah, Jorge C.; Eggers, Scott D.; Bach, Sarah E.; Dubey, Divyanshu; McKeon, Andrew B.
Abstract : Abstract: A 45-year-old man with a history of testicular seminoma treated 8 years earlier presented with chronic progressive truncal and limb ataxia, progressive sensorineural hearing loss, and episodic vertigo. Eye movement and neuro-otology examinations showed localizing abnormalities to the bilateral cerebellar flocculus, vermis, and bilateral cerebellar hemispheres. Audiometric testing showed bilateral symmetric sensorineural hearing loss. There was a normal MRI of the brain. Cerebrospinal fluid (CSF) showed modest lymphocytic pleocytosis, and there was an elevated serum choriogonadotrophic hormone. An abdominal CT scan showed a solitary, large retroperitoneal lymph node, and histopathologic examination of the node biopsy showed granulomatous inflammation without microorganisms; eventually, immunohistochemical markers confirmed the diagnosis of metastatic seminoma. Although normal neuroimaging and inflammatory CSF reaction suggested a paraneoplastic etiology, the initial paraneoplastic antibody testing was negative. Subsequent investigation identified a positive kelch-11 protein antibody, thus confirming the paraneoplastic connection between the metastatic seminoma and the subacute neurologic–cochleovestibular syndrome. Abstract : Supplemental Digital Content is Available in the Text.